EXPLORATION IN BODY EXERCISE COURSE AS A SOURCE OF INSPIRATION FOR MOTION IN THE CREATION OF DANCE WORKS (CHOREOGRAPHY) - Romi Nursyam; Setiawati, Rahmida (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2023)
The aim of the research is to find out about the exploratory process in body sports courses to produce movement in creating dance works and to find out other factors that influence exploration, such as imagination, intuition, and creativity. The research method used is based on the problem to be solved, beginning with a study of the choreography development of Dance Program students using qualitative descriptive methods. The results of research conducted at Universitas Negeri Jakarta (UNJ) with the object of dance art education program students. The exploration process in body exercise courses can be a source of inspiration for movement through imagination, intuition, and creativity so that students are able to create dance works with varied movements. It is expected to support the research results. So that it can be used as an appreciation of motion and music as student choreography learning. A form of exploration of motion, through imagination, intuition, and creativity as a reflection of the student's body in expressing motion. students gain the discovery of personal movements so that during the choreography learning process students can feel the freedom of learning fun creative movements. Furthermore, students find movements that are appropriate to wiraga, wirama, wirasa, and beautiful movements.